2015
DOI: 10.19168/jyu.00944
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration Likelihood Model (ELM) In Print Advertisements: A Content Analysis of Advertisements Which Is Positioned In Special and General Interest Magazines

Abstract: Öz: Detaylandırma Olasılık Modeli ikna edici iletişime yönelik oldukça açıklayıcı bir yapıdır ve ikna edici iletişim sürecini iki rota veya yol üzerindenaçıklamaktadır. Bu çalışma, özel (tematik)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…The quality of the argument in the ELM study has 2 components, the strength of the argument and the direction of the argument [15]. The Elaboration Likelihood Model (ELM) is the main theory in the field or realm of persuasive communication [16] which has been widely used by researchers, such as Durmaz and others [17] in print media advertising which found that readers are segmented into special interest/theme magazines and general magazine. Magazines with special interests/themes are hit by more arguments than magazines with general themes.…”
Section: Elaboration Likelihood Model (Elm)mentioning
confidence: 99%
“…The quality of the argument in the ELM study has 2 components, the strength of the argument and the direction of the argument [15]. The Elaboration Likelihood Model (ELM) is the main theory in the field or realm of persuasive communication [16] which has been widely used by researchers, such as Durmaz and others [17] in print media advertising which found that readers are segmented into special interest/theme magazines and general magazine. Magazines with special interests/themes are hit by more arguments than magazines with general themes.…”
Section: Elaboration Likelihood Model (Elm)mentioning
confidence: 99%